Pengaruh Kualitas Layanan dan Citra Perusahaan terhadap Loyalitas Nasabah pada PT. BPR Sari Jaya Sedana di Klungkung - Kadek Novita Maharani Dewi; A.A. Ketut Jayawarsa; A.A. Sri Purnami (Warmadewa Economic Development Journal (WEDJ), 2019)
The aims of this research is to know the influence of the quality of service and customer loyalty towards the company's image simultaneously and partial on BPR Sari Jaya Sedana. Samples become the object of the research is the customer on BPR PT Sari Jaya Sedana. The analysis of the data used is test validity and reliability, test the assumptions of classical linear regression method, and multiple. The results showed that the simultaneous service quality and corporate image of the positive effect significantly to customer loyalty. Then partially also the service quality and corporate image of the positive effect significantly to customer loyalty.